Apollinaire et l'esthétique de la perte - Fraisse, Luc (Wydawnictwo Naukowe UAM, 2007)
Does aesthetics of loss exist? What can we lose when we give vent to our poetic creative activity? These questions are posed by Apollinaire in the three verses of the Calligrammes collection, used to interpret the Alcools collection: "To lose/But to lose truly/ In order to make room for revelation." Accordingly, what does the experience of creative loss consist in? It is about emphasizing all this that can be lost in a poetic text in order to see that loss can become a creative process once it turns out to be impossible, and that poetic revelation can only take place in a situation when we lose something. Apollinaire was distrustful of all explicit poetic manifestos; therefore, the answers full of nuances should be sought in the dim light of Alcools and its interpretations.
Apollinaire and aesthetics of loss
Keywords: Apollinaire; Calligrammes collection; Alcools collection